The Enforcement of Disciplinary Sanctions Against Civil Servants Based On Law Number 20 Of 2023 - Salahudin, Salahudin; Hasanah, Siti; Jiwantara, Firzhal Arzhi (Faculty of Law, Universitas Pekalongan, 2024)
The concept of applying disciplinary consequences against Civil Servants (PNS) in accordance with Law Number 20 of 2023 is discussed in this article. In this article, a review of this statute is used to investigate essential aspects of the enforcement of disciplinary sanctions against civil officials. These features include the procedures that must be executed. subsequently, the categories of infractions that may be subject to disciplinary sanctions, as well as the sanctions that may be applied during the course of the violation. In order to maintain discipline and integrity in the work environment of civil servants, as well as to enforce applicable legal restrictions, it is essential to have the notion of implementing disciplinary consequences. Within the context of this discussion, this article also addresses the difficulties that may be encountered when enforcing disciplinary sanctions, as well as the efforts that are being made to improve the efficiency of the system that is used to enforce disciplinary sanctions. In the hopes of achieving a more professional, transparent, and accountable working environment among public officials, it is believed that a more in-depth understanding of the notion of imposing disciplinary sanctions would be attained